Factors determining the direction of the process of physical rehabilitation of men with osteochondrosis of the lumbar spine in remission - Rymma Bannikova; Volodymyr Kormiltsev; Victoria Brushko; Mariia Balazh (Kharkiv State Academy of Physical Culture, 2019)
Purpose: identify relationships based on the results of clinical, biomechanical and functional data to identify the main factors influencing the nature and direction of the process of physical rehabilitation of men with osteochondrosis of the lumbar spine in remission. Material & Methods: analysis of special scientific and methodical literature; content analysis of medical records, results of computer tomograms and radiographs; clinical research methods; pedagogical research methods; biomedical research methods; computer photometry; methods of mathematical statistics. In the analysis of medical records (n=60), data of men of the second adult age were used with a diagnosis of osteochondrosis of the lumbar spine in the stage of incomplete and complete remission. Results: representatives of the studied population constitute a level of pain in visual analogue scale (VAS) below the average, and during periods of exacerbation of the disease, this indicator is above 50%. After testing the musculoskeletal system according to the method of A. V. Vasilenko, a result was obtained that corresponds to a low level. During the Romberg test, a tendency to a decrease in vertical stability was observed, which may be due to the increased angles of the biogeometric posture profile. During the analysis of heart rate variability, the mode amplitude index in the examined population was 78,1±5,5% (͞Х±S), which indicates the prevalence of moderate sympathicotonia. Conclusion: in the course of factor analysis, four factors were identified that affect the nature and direction of rehabilitation measures and describe 77,33% of the total variance. The most informative and significant indicators for this category of patients, which characterize each factor, were determined.